IRRIGATION SYSTEM FOR LOW COST IN URBAN CENTERS NURSERIES - PUTTI, Fernando F. Ferrari; GABRIEL FILHO, Luís R. A.; BONINI NETO, Alfredo; BONINI, Carolina Dos S.; CREMASCO, Camila P.; KLAR, Antonio E. (Revista Brasileira de Engenharia de Biossistemas, 2013)
The necessity to reduce the water consumption in urban centers is of fundamental importance due to prolonged droughts. Thus, it is necessary the utilization sustainable and conscious of the usage in irrigation of orchidarium in urban centers. Regarding the problem, the paper aimed to perform the demonstration of costs and feasibility of implementing of irrigation systems of low cost destined the irrigation of small orchidarium in urban centers. The prototype was developed in an orchidarium localized in Botucatu city, where were used all the materials involved. It should be noted that the system does not have pump to pressurize the system and only the pressure, from the water supplier. Thus, it can be noted that the final cost was low, and the system presents to be efficient and consistent with the needs for a small irrigation system.